Inferential reasoning of high school mathematics teachers about t-Student statistic - Lugo-Armenta, Jesús Guadalupe (2022)
One of the topics that have been deeply studied in Statistical Education is that of how to promote formal inferential reasoning (FIR) based on the results of informal inferential reasoning (IIR). However, it is still necessary to have proposals to explore and progressively develop the inferential reasoning of students and teachers from IIR to FIR. In this context, this article seeks to characterize the inferential reasoning displayed by high school mathematics teachers in the practices they developed for solving problems about Student’s t statistic. To do this, we use theoretical and methodological notions introduced by the Onto-Semiotic Approach (OSA) to mathematical knowledge and instruction, among which are the notion of mathematical practice, mathematical object and the theoretical proposal of progressive levels of inferential reasoning about the Student’s t statistic. The subjects who participated in this qualitative study were 59 teachers in training from Costa Rica and 22 practicing teachers from Chile. The practices developed by the pre-service teachers and the practicing teachers were found to have similar elements (representations, concepts/definitions, properties, procedures, arguments). The principal conclusion of this investigation was that the proposal of inferential reasoning levels about Student’s t statistic proved to be a useful predictor of the practices developed by the teachers, making it possible to distinguish characteristic elements of each level of inferential reasoning.